Active Methanotrophs in Suboxic Alpine Swamp Soils of the Qinghai–Tibetan Plateau - Mo, Yongliang; Qi, Xing-e; Li, Aorui; Zhang, Xinfang; Jia, Zhongjun (Frontiers in Microbiology, 2020)
Methanotrophs are the only biofilters for reducing the flux of global methane (CH4) emissions in water-logged wetlands. However, adaptation of aerobic methanotrophs to low concentrations of oxygen and nitrogen in typical swamps, such as that of the Qinghai–Tibetan Plateau, is poorly understood. In this study, we show that Methylobacter-like methanotrophs dominate methane oxidation and nitrogen fixation under suboxic conditions in alpine swamp soils. Following incubation with 13C-CH4 and 15N-N2 for 90 days under suboxic conditions with repeated flushing using an inert gas (i.e., argon), microbial carbon and nitrogen turnover was measured in swamp soils at different depths: 0–20 cm (top), 40–60 cm (intermediate), and 60–80 cm (deep). Results show detectable methane oxidation and nitrogen fixation in all three soil depths. In particular, labeled carbon was found in CO2 enrichment (13C-CO2), and soil organic carbon (13C-SOC), whereas labeled nitrogen (15N) was detected in soil organic nitrogen (SON). The highest values of labeled isotopes were found at intermediate soil depths. High-throughput amplicon sequencing and Sanger sequencing indicated the dominance of Methylobacter-like methanotrophs in swamp soils, which comprised 21.3%–24.0% of the total bacterial sequences, as measured by 13C-DNA at day 90. These results demonstrate that aerobic methanotroph Methylobacter is the key player in suboxic methane oxidation and likely catalyzes nitrogen fixation in swamp wetland soils in the Qinghai–Tibetan Plateau.